PENENTUAN SIFAT LISTRIK AIR PADA WADAH ALUMINIUM DAN BESI BERDASARKAN PENGARUH RADIASI MATAHARI - Yusuf Syetiawan; Sugianto '; Riad Syech (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
A  research has been conducted  to  determine  the electrical properties  of water  in  an aluminum and  iron  containers.  The  waters  used  were  well  and  rain  water using  metaland  aluminum  containers.  This research was conducted  using  an experimental method. The results showed  that  the  best  electrical properties  was  found from  rain  water  in the aluminium  container  with its  resistivity  of  18.294m ,  electrical  power  of  0.00046  W, electrical energy  of  2,941  J  and  electrical  conductivity  of  0.055  (1)m.  The  resultsindicated  that  greater  solar radiation  in  the  water  could  produce  of  electrical properties greater  than  that  of water  on  the electrical  properties of  the electrical  resistivity.The affecting factor of electrical  properties of  the rain  water  was  concentration  of  Fe  and  Cu. The  concentrations  of  Fe  and  Cu  in  rain  water  was  0,065  ppm  and  0,050  ppm.  It was also found that  the smaller  the  concentrations of  Fe  and  Cu  levels  in  solution  was  the purer the solution.